ZAKAT AND TAX; FROM THE SYNERGY TO OPTIMIZATION - Mustofa, Mustofa; Fata, Khoirul (Al-Ulum, 2015)
Dualism dilemma between zakat and tax in Indonesia can be relatively mitigated by ratification of Act No. No. 38/1999 on Management of Zakat. In the regulation, zakat has been synergized with tax by placing zakat as a deduction from taxable income element (PKP). But so far it has not been given the significant impact on the acceptance of zakat and awareness of Muslims to pay zakat. There are also some problems in practical level that contribute to that fact. This article explores the zakat and tax synergy that have been achieved through Act No. 38 of 1999, the problems found in its execution, and of course an offer for a solution to optimize the role of zakat and tax for the people welfare. By examining same practice in some countries, this paper recommends zakat as a direct tax deduction (tax credit) as a strategic step in the effort to optimize the role of zakat.-----Dilema dualisme zakat dan pajak di Indonesia relatif bisa diredakan melalui pengesahan Undang-undang No No 38/1999 tentang Pengelolaan Zakat. Dalam peraturan itu zakat telah disinergikan dengan pajak dengan menempatkan zakat sebagai unsur pengurang Penghasilan Kena Pajak (PKP). Namun sejauh ini ketentuan itu belum memberi pengaruh yang signifikan bagi penerimaan zakat maupun kesadaran umat Islam untuk membayar zakat. Selain itu juga terdapat problem di tingkat praktis yang turut berperan bagi kenyataan itu. Tulisan ini mencoba membahas sinergi yang telah tercapai melalui UU No 38 tahun 1999, problem-problem yang ditemukan dalam pelaksanaannya, dan tentu saja tawaran bagi solusi optimalisasi peran zakat dan pajak bagi kesejahteraan rakyat. Dengan mengkaji praktik di beberapa negara, tulisan ini merekomendasikan zakat sebagai pengurang pajak secara langsung (tax credit) sebagai langkah strategis dalam upaya optimalisasi peran zakat.